Dewesternising the South African social security law: a leap towards an Afrocentric legal curricular - Shelton Tapiwa Mota Makor; Nombulelo Lubisi (De Jure, 2021)
Recent calls to dewesternise the curricular are especially pertinent to the teaching of Social Security Law in South Africa, which has traditionally been dominated by the Eurocentric canon. This article argues that South African Social Security Law is a western-centric phenomenon and dewesternising it is necessary for the decolonisation of legal education. On this score, it provides a critique of the South African Social Security Law in search of pragmatic ideas that can advance the project of decolonising it and creating Third World perspectives. The article unsettles the dominant Eurocentric model on the origin of South Africa Social Security Law which marginalise the role that indigenous knowledge play in the development of this area of law. It argues that placing indigenous knowledge systems on the epicentre of the historiography of teaching South African Social Security Law will lead to some epistemic disruption of the current historic paradigm, a project necessary for the decolonisation of the legal mind and intellectual landscape. The article re-contextualising the orthodox social security theory in the historical scene of colonial and post-era; constructing alternative social security historiography; offering an Africanised dialogue on the origins of the informal strands of social security law; the elaboration of alternative methodologies of actualising the constitutionally protected right to have access to social security. The paper also contends with concepts and ideas such as the deemed trans-colonial importation of social security origins, decolonial philosophy as an epoch of transforming legal education in the context of South African Social Security Law.